Melestarikan Budaya Lokal melalui Film: Analisis Tekstual Seni Budaya Ludruk pada Loka Drama Lara Ati di Vidio - Kurniastuti, Harisanti (VISA: Journal of Vision and Ideas, 2024)
This research is about, the art of the culture put on the playground of Lara Ati on the Platfrom Vidio in order to preserve the local through the film. The researchers are interested in doing research into the representation of local culture of ludruk present in the youth series titled Lara Ati. Researchers want to know how local culture ludruk is represented through films. The author carries out research into Ludruk culture in eastern Java through the Lara Ati drama site using Textual Analysis. Textural Analysis is the analysis of discourse that focuses internally on dictated and viewed texts of form (cohesion) and meaning. (koherensi). On the stage of the drama, Lara Ati tells about everyday life that is shown in the local language. In the playground, Lara Ati also featured a copy of the ludruk art that was on episode 16-17. The result of this research is with the presence of Loka Drama Lara Ati generation now begins to know about the Ludruk art through the media Film on the Vidio application.